Pengendalian Internal, Komitmen Organisasi, Kesesuaian Kompensasi dan Kecenderungan Kecurangan Akuntansi - Deasri, Ni Kadek Dwita; Utama, I Made Karya (E-Jurnal Akuntansi; Vol 32 No 8 (2022), 2022)
This study aims to analyze the effect of internal control, organizational commitment, and suitability of compensation on the tendency of accounting fraud. The research was conducted at KSP in Gianyar Regency. The theory used is attribution theory. The number of samples used as many as 59 people with purposive sampling method. The data collection used is a survey. Data analysis used multiple linear regression analysis. The findings show that internal control, organizational commitment, and compensation suitability have a negative effect on the tendency of accounting fraud. So, it can be concluded that the better the internal control, organizational commitment, and suitability of compensation at KSP, it can minimize the potential for accounting fraud in KSP in Gianyar Regency. Keywords : Internal Control; Organizational Commitment; Compensation Suitability; Tendency of Accounting Fraud